Persetujuan Khuluk Sebab Pengaruh Jin: Studi Kasus Satu Keluarga di RT. 038 Kelurahan Melayu Kecamatan Tenggarong - Faishol, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
Khuluk is a divorce lawsuit that comes from the wife by requiring that the plaintiff must declare the lawsuit in a conscious condition. The husband as the defendant cannot approve the lawsuit if the wife does not meet the requirements for submitting khuluk, but not in one family in the RT. 038 where the wife who proposes khuluk is under the influence of a jinn. The research method used is qualitative research. The type of research used is a case study. Khuluk that happened in RT. 038 took place in a condition where the wife was influenced by the jinn, where at that time her husband did not immediately agree to the khuluk lawsuit so that the legal review of this case was divided into two parts. The first part is that the condition of the wife who does not meet the requirements of the plaintiff of khuluk is considered invalid, while the second part is the reason why the husband agreed to the lawsuit which was analyzed through several fiqh rules and sadd aż-żarāi' was considered legal.